Controlled trial comparing olsalazine and sulphasalazine for the maintenance treatment of ulcerative colitis. - Ireland, A; Mason, C; Jewell, D (1988)
One hundred and sixty four patients with ulcerative colitis in remission were entered into a double blind, double dummy trial comparing olsalazine 500 mg bd and sulphasalazine 1 g bd. Clinical examination, sigmoidoscopy and rectal biopsy were performed at 0, three, and six months. Sixteen of 82 (19.5%) patients relapsed on olsalazine and 10/82 (12.2%) relapsed on sulphasalazine. The difference was not statistically significant (p = 0.1632). Adverse events were minor and were similar in both groups. No haematological or biochemical abnormalities were detected. Thus, olsalazine is as effective as sulphasalazine for preventing a relapse of ulcerative colitis.